Binding and endocytosis of erythrocytes sensitized with rabbit IgG via Fc gamma receptors of human monocytes. - Kávai, M (1991)
The properties of the monocyte Fc gamma receptors (FcR) were investigated with monoclonal antibodies (mAb) against FcRI (10.1) and FcRII (IV3). mAb against FcRI inhibited partially the binding of sheep red blood cells (SRBC) sensitized with anti-SRBC rabbit IgG (EA) at 37 degrees to monocytes pretreated with N-ethyl maleimide, which inhibits the EA ingestion. The erythrocytes (E) were sensitized with varying concentrations of anti-E rabbit IgG. The EA binding to different FcR depends on the concentration of specific antibody used to sensitize the erythrocytes. At high levels of sensitization a high proportion of rosettes form via FcRII which can be inhibited with mAb IV3. As sensitization decreases it is more difficult for FcRII to form rosettes, so an increased percentage of them is mediated via FcRI. Sensitization of SRBC with 1-1.5 x 10(3) anti-SRBC rabbit IgG molecules per erythrocyte is the threshold to allow FcRII to mediate rosettes. At the lowest levels of sensitization the total number of rosettes is even lower and all rosettes are mediated via FcRI, hence mAb 10.1 is fully inhibitory. In addition, our data strongly support the view that the ingestion of EA takes place mainly via FcRII. We show in this study that while binding of slightly sensitized erythrocytes was blocked efficiently by mAb 10.1, the ingestion of the equivalent EA was hardly inhibited by it.